Dan Pengaruh Capital Intensity, Profitabilitas dan Corporate Social Responsibility Terhadap Agresivitas Pajak: Studi Kasus Pada Perusahaan Sub Sektor Property dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Ragita Dwi Cahya; Meta Nursita (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to test and prove the effect of capital intensity, profitability and corporate social responsibility on property and real rstate sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The type of research used in this study is quantitative. The data used is secondary data in the form of an annual report. The sampling technique used is the purposive sampling method. The population in this study is property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period, totaling 87 companies. The sample used in this study was 11 companies with 5 years of research, the total data of this study was 55 companies. Hypothesis testing in this study used regression analysis of panel data using E-views 9 software. The results of the study simultaneously show that the variables of capital intensity, profitability and corporate social responsibility have an influence on tax aggressiveness. And the results of the study partially show that the capital intensity variable and the corporate social responsibility variable affect tax aggressiveness, while the profitability variable does not affect tax aggressiveness.